(untitled) (Revista de História da UEG (REVHIST), 2023)
The present text aims to point out some aspects of the History of Black American Cinema and the impact of its resistant and revolutionary narratives in Hollywood cinema of white supremacy, with this objective also bringing as a proposal of continuity of this resistance an analysis about the film Infiltrated in the Klan (2018), by filmmaker Spike Lee, based on the racial issue. Finally, draw a historical parallel present in the film with the perspective of analyzing it in the classroom through the use of the film as a source for teaching History considering the guidelines of Law 11.645/2008. Keywords: American Black Cinema. Race issue. Law 11.645/2008.